2009
DOI: 10.1002/jcla.20286
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and calcium in exhaled breath condensate of children with asthma and gastroesophageal reflux disease

Abstract: Background: Magnesium and calcium physiologic functions are closely related. Magnesium is primarily an intracellular cation, the action of which also involves maintenance of cellular ionic balance, while influencing calcium homeostasis by blocking calcium channels. The aim of this study was to compare the concentrations of magnesium and calcium in exhaled breath condensate (EBC) of children with asthma and gastroesophageal reflux disease (GERD).Subjects and methods: EBC was collected from 66 children aged 7–14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Calcium (Ca 2+ ) acts as an activator of airway smooth muscle contractions (25), and magnesium has a role in smooth muscle relaxation (26). Our previous study indicated the close inter-reactivity of calcium and magnesium in both asthmatic and GERD patients (12). The present study results demonstrated that in both groups of patients, acidification mechanisms exceeded the physiological-buffering capacity of the airways, resulting in lower EBC pH than in clinically healthy controls.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Calcium (Ca 2+ ) acts as an activator of airway smooth muscle contractions (25), and magnesium has a role in smooth muscle relaxation (26). Our previous study indicated the close inter-reactivity of calcium and magnesium in both asthmatic and GERD patients (12). The present study results demonstrated that in both groups of patients, acidification mechanisms exceeded the physiological-buffering capacity of the airways, resulting in lower EBC pH than in clinically healthy controls.…”
Section: Discussionsupporting
confidence: 56%
“…In previous investigation we have reported the occurrence of close inter-reactivity between calcium and magnesium in EBCs of children with asthma and gastroesophageal reflux disease (GERD) (12). Studies in animals have shown that the acidification of the airways was associated with bronchoconstriction (13) As acidification of the airways causes bronchoconstriction, the aim of the present study was to find out whether there is any difference in calcium and magnesium in EBC of children with uncontrolled asthma (i.e., with endogenous acidification) and children with GERD (i.e., with exogenous acidification).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium, in addition to its bronchodilator effect, also plays a role in inflammation, oxidative stress and the apoptosis process. Decreased magnesium intake results in an increase in cytokines and reactive oxygen species, increased phagocytosis and the start of the pro-inflammatory process 16 . Magnesium deficiency may be related with increased inflammatory process and smooth muscle contractility.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were a few studies on asthma. The magnesium level is generally evaluated by measuring serum levels of magnesium and there are a few studies at tissue level 16,18 . Because serum magnesium measurement does not reflect the magnesium levels in the body, researchers tend to measure levels of magnesium in cells such as leukocytes, and erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The magnesium to calcium ratio, however, was lower in both children with asthma and those with GER. The later and larger study found calcium and magnesium to be elevated among children with GER, and inversely related to the EBC pH [9, 11]. Another study found levels of chloride to be lower in the EBC of 5 GER-induced chronic cough patients compared with 16 healthy controls [22].…”
Section: Exhaled Breath Condensate Biomarkersmentioning
confidence: 99%